Understanding creativity in early childhood meaning-making and children's drawings - Wright, Susan Kay (London SAGE, 2010)
Creativity is a key theme in early childhood studies at the moment & is increasingly highlighted in all manner of early childhood academic courses. This book will form the link between creativity & literacy with concrete examples of children?s meaning making, as well as offering a protocol for students to follow.
Keywords: Creative ability in children -- Study and teaching (Early childhood); Drawing